Hypomagnesemia - A New Perspective - Jaswant Kaur; Jaspreet Kaur; Navdeep Kaur; Tejinder Singh; Deepika Dalaal (Current Innovations in Medicine and Medical Science Vol. 5, 2022)
Hypomagnesemia means a significant decrease in magnesium in the body. Its most commonly seen in patients with diabetes mellitus-associated complications. The aim of the study is to determine the levels of magnesium in diabetes mellitus, and its associated disease, in cardiovascular and cerebrovascular patients. Diabetes Mellitus is not a single disease entity, but rather a group of metabolic disorders sharing common features of hyperglycemia. One of the major complications of diabetes mellitus (DM) is cardiovascular disease (CAD), which is the foremost cause of death in patients of north India. Magnesium acts as an intracellular electrolyte that helps regulate calcium influx and potassium outflow, enabling the cardiac muscle to survive during ischemia.In the Atherosclerotic Risk in Communities [ARIC] study, serum magnesium levels were inversely related to the incidence of hypertension and stroke. Hence, serum magnesium levels are lower in hypertension and diabetes mellitus, both of which are risk factors for stroke. Several findings may exhibit the extent of deficiency of magnesium as a trace element about the duration of the disease. It may be utilized to optimize the control of type-2 diabetes mellitus by supplementation of magnesium. This chapter provides an overview of early hypomagnesemia management to reduce the risk of diabetes mellitus and its complications. By doing so the metabolic complications of diabetes mellitus can be delayed.